2013
DOI: 10.1007/s10067-013-2305-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of S100A8 and S100A9 in patients with diffuse cutaneous systemic sclerosis. A correlation with organ involvement and immunological abnormalities

Abstract: S100A8 and S100A9 play important roles in immune and inflammatory disorders. The role of the two proteins in systemic sclerosis (SSc) remains unknown. Fifty-seven diffuse cutaneous SSc (dcSSc) patients, 31 limited cutaneous SSc (lcSSc) patients were recruited in the present study. The expression of S100A8 and S100A9 in plasma was measured using an enzyme-linked immunosorbent assay and the mRNA levels in peripheral blood were assessed using reverse transcriptase quantitative PCR. The expression and distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 26 publications
2
40
0
3
Order By: Relevance
“…The discrepancy between the correlation in patients with lcSSc versus dcSSc is however remarkable. Especially in the light of the recent publication showing S100A8/A9 being increased mainly in the dcSSc population, this might be explained due to differences between Asian and Caucasian populations or differences in inclusion criteria and/or technicalities of the ELISAs used 19. Earlier studies have shown an increase in SSc patient without making a subdivison 20 21.…”
Section: Discussionmentioning
confidence: 98%
“…The discrepancy between the correlation in patients with lcSSc versus dcSSc is however remarkable. Especially in the light of the recent publication showing S100A8/A9 being increased mainly in the dcSSc population, this might be explained due to differences between Asian and Caucasian populations or differences in inclusion criteria and/or technicalities of the ELISAs used 19. Earlier studies have shown an increase in SSc patient without making a subdivison 20 21.…”
Section: Discussionmentioning
confidence: 98%
“…Paquinimod binds to S100A9 and inhibits its binding to the pro-inflammatory receptors RAGE and TLR4 [15]. S100A9 may be directly involved in the fibrotic events occurring in SSc patients as S100A9 has been shown to stimulate proliferation and production of collagen by fibroblasts via binding to RAGE [19,27], but an indirect role where S100A9 affects innate immunity in the skin is however also possible. For example, mice lacking S100A9 have an impaired recruitment of myeloid cells to a wound, resulting in faster wound closure and less scar tissue formation [28].…”
Section: Discussionmentioning
confidence: 96%
“…The S100A9 protein has been identified as one target molecule for paquinimod [15]. S100A9 is involved in both activation and recruitment of myeloid cells into inflammatory sites [16] and a pro-inflammatory role for S100A9 is supported by elevated levels of S100A9 in several autoimmune/inflammatory diseases, including SSc [17][18][19]. Extracellular S100A9 acts as a damage-associated molecular pattern (DAMP) that interacts with a number of receptors, including toll-like receptor 4 (TLR4) and the receptor for advanced glycation end-product (RAGE) which are typical pattern recognition receptors expressed on cells within the myeloid compartment.…”
Section: Introductionmentioning
confidence: 99%
“…Their levels are higher in sera and bronchoalveolar lavage fluid from SSc patients. 101, 102 An independent study found increased levels in lcSSc patients with lung fibrosis and Scl70 positivity, but observed no correlation to pulmonary function tests. 103 Further studies are required to identify and validate specific biomarkers and their roles in pathogenesis, and to enable early prediction of patients who will need a lung transplant.…”
Section: Systemic Sclerosis (Ssc Scleroderma)mentioning
confidence: 98%